The Role of Branding in Developing Sustainable Fashion Brands: A Systematic Literature Review and Bibliometric Analysis - Farida, Lailatul (International Journal of Economics Development Research (IJEDR), 2024)
This study examines Generation Z's behavior in purchasing second-hand clothing on Instagram, focusing on socio-environmental awareness, preconception, frugality, brand awareness, social prestige, need for uniqueness, scarcity, and perceived competition. Using a quantitative method with 312 respondents aged 17-27, the findings reveal that socio-environmental awareness, social prestige, scarcity, and perceived competition positively influence purchase intention, while brand awareness and preconception have negative effects. Need for uniqueness and frugality are not significant factors. Purchase intention positively affects purchase behavior. The study suggests that sellers should emphasize environmental aspects and scarcity to attract Generation Z consumers.